Transforming Mustahik Partners to Muzakki Strategy: Case Study on BAZNAS Microfinance Desa, Sawojajar, Malang City (UIN Sunan Kudus, 2023)
BAZNAS Microfinance Desa is a microfinance service that has an important role in facilitating access to capital, providing business assistance, and facilitation to micro-business actors. This study aims to find out the strategy implemented by BAZNAS Microfinance Desa in transforming Mustahik Partners to Muzakki in Sawojajar Malang. The type of research used is qualitative research with a case study approach. The data used are primary and secondary data. Primary data collection was obtained from the results of interviews. While secondary data is in the form of observation, and documentation. This documentation is in the form of evidence of records or historical reports that have been compiled in archives, journals, and literature relating to the data of mustahik partners who become muzakki after receiving capital assistance at the BAZNAS Microfinance Desa. This study uses data validity techniques using a triangulation model. Data analysis techniques used in this study are data collection, data condensation, data presentation, and drawing conclusions. The results of the study show that the strategy of BAZNAS Microfinance Desa at Sawojajar Malang is to increase the status of mustahik to become muzakki. In an effort to be able to improve and change the status of partners who initially had to change to muzakki, they had to implement several strategies including planning a partner feasibility study, conducting outreach, forming groups, looking at the feasibility study of partners who had just joined BAZNAS Microfinance Desa, and finally completing a capital financing assessment. business and distribution of funds. This research contributes to finding out the alternative strategy to transform mustahik become muzakki by enhancing their income of business.